Shocks and the determinants of resilience: Fish and shrimp value chains in Bangladesh after Covid-19 - Kabir, Razin; Bin Khaled, Muhammad Nahian; Narayanan, Sudha; Rashid, Shahidur (Wiley, 2023)
There is little systematic evidence on the resilience of South Asian agri‐food value chains since the onset of Covid‐19. Using two rounds of surveys of 1751 fish and shrimp value chain actors in Bangladesh, this paper undertakes two sets of tasks: (a) analyzes business continuity (closures and resumptions) and its implications for household food security, and (b) adapts a ten‐item measure of subjective resilience and examines its predictors: diversity, scope, scale, vertical integration, and cluster effects. Results show that recent closures are linked to Covid‐19, suggesting that firms were only able to sustain operations for a period of 8–9 months before folding due to cumulative stresses; and that the degree of resilience varies significantly across value chains and the segments within them. Interestingly, contrary to established stylized facts, clusters appear to be negatively correlated with resilience, indicating that cooperation among value chain actors within a cluster breaks down under large‐scale covariate shocks. The implications of these and other key findings are discussed.